South Africa : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
South Africa showed strong macroeconomic performance owing to its sound policies, which aimed at raising economic growth and reducing poverty, within a stable macroeconomic, social, and political environment. Executive Directors commended the strong economic performance, sustainable fiscal policies, and sound debt management that helped to reduce public debt. They appreciated the authorities' efforts on addressing major economic and social challenges while preserving macroeconomic stability. They agreed that the flexible exchange-rate system and sound financial system has helped the country to sustain economic growth.